Comparison between Endoloop-Assisted Endoscopic Resection and Endoscopic Submucosal Dissection for Large Pedunculated Polyps - Lu, You-Zhu (Journal of Digestive Endoscopy, 2024)
Background Endoscopic resection of large pedunculated colorectal polyps with a thick stalk is technically difficult. Endoloop-assisted endoscopic resection and endoscopic submucosal dissection have been confirmed to be effective and safe, respectively. Here, we compared the efficacy and safety of these two different methods.Methods In total, 124 patients with large pedunculated polyps treated by endoloop-assisted endoscopic resection (group B) or endoscopic mucosal resection (group A) were enrolled in the study.Results There were two cases of immediate postpolypectomy bleeding and one case of delayed postpolypectomy bleeding in group A, while there were four cases of immediate postpolypectomy bleeding and 0 case of delayed postpolypectomy bleeding in group B. There was no significant difference in postpolypectomy bleeding between the two groups (p = 0.68 and 1.0). The mean operation time in group A was 29.31 ± 5.64 minutes, which was significantly longer than that in group B (p < 0.001). The mean hospitalization time in group A was 7.14 ± 1.1 days, but in group B it was 5.98 ± 1.18 days (p < 0.001). In addition, the number of clips used in group A was 5.58 ± 1.3, which was also more than that in group B (p < 0.001).Conclusions Endoloop-assisted endoscopic resection is effective and safe for the removal of large pedunculated polyps, while endoscopic submucosal dissection may be an alternative option for difficult areas with poor visibility or polyps with large or lobulated head.
Keywords: endoloop-assisted endoscopic resection; endoscopic submucosal dissection; large pedunculated polyps